2018
DOI: 10.3390/educsci8040191
|View full text |Cite
|
Sign up to set email alerts
|

From High School Access to Postsecondary Success: An Exploratory Study of the Impact of High-Rigor Coursework

Abstract: Educators and policymakers are keenly aware of the need to prepare students to compete in an increasingly global society. It is widely accepted that a high school diploma is not sufficient and that secondary schools have a responsibility to prepare students to be college and career ready. This study examined participation in a rigorous secondary curriculum and the corresponding outcomes related to college enrollment, persistence, and graduation. Focusing on the involvement of students in high-rigor courses tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…This study is one of the first of its kind to conduct an intersectional analysis of AP Chemistry coursetaking and achievement in precollege settings. This work is consequential given the importance of high school coursework in predicting postsecondary STEM persistence, degree completion, and socioeconomic advancement. The identification of these disparities may inform systemic efforts to reduce inequities in precollege STEM access and performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is one of the first of its kind to conduct an intersectional analysis of AP Chemistry coursetaking and achievement in precollege settings. This work is consequential given the importance of high school coursework in predicting postsecondary STEM persistence, degree completion, and socioeconomic advancement. The identification of these disparities may inform systemic efforts to reduce inequities in precollege STEM access and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and education policy makers at all levels (federal, state, local) have prioritized college preparation and workforce readiness, highlighting the importance of rigorous high school coursework . Research has shown college enrollment and degree completion are more likely for students who have taken advanced coursework in science and mathematics in high school. Students taking advanced precollege coursework also have higher earnings after graduation, regardless of race . Chemistry is considered a rigorous high school course that prepares students for college-level coursework, yet just 70% of high school students complete a chemistry course before graduation .…”
Section: Introductionmentioning
confidence: 99%
“…Readiness in the context of college and career readiness has been determined to be a critical measure, and factors such as involvement in high-rigor courses in a secondary curriculum are linked to outcomes in college enrollment, persistence, and graduation. Studies show that participation in college preparatory coursework and gateway courses, has a direct correlation with postsecondary outcomes [5]. These secondary preparatory courses also provide an opportunity for students to apply skills associated with time management, stress management, and how to study [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that participation in college preparatory coursework and gateway courses, has a direct correlation with postsecondary outcomes [5]. These secondary preparatory courses also provide an opportunity for students to apply skills associated with time management, stress management, and how to study [5]. Secondary preparation courses and gateway courses and the measures associated with them have become important measures for student's college and career readiness, although additional research is needed to look further at various types of education institutions and career opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Course‐taking can be described using the quantity (i.e., the number of credits received) and the quality (how advanced the course is) of the courses taken (Adelman, 2006). Studies show that both the quantity and quality of academic courses completed in high school are strong predictors of secondary and postsecondary attainment and success (Adelman, 2006; Leow et al., 2004; Long et al., 2012; Morgan et al., 2018).…”
mentioning
confidence: 99%